Laboratory Scale Brachionus plicatilis Culture Technique with Natural Feeds Nannochloropsis oculata and Tetraselmis chuii in Marine Aquaculture Center Lampung, Teluk Pandan, Pesawaran: Laboratory Scale Brachionus plicatilis Culture Technique with Natural Feeds Nannochloropsis oculata and Tetraselmis chuii in Marine Aquaculture Center Lampung, Teluk Pandan, Pesawaran - Ramadhani, Desvita Putri; Maretta, Gres (MAXIMUS: Journal of Biological and Life Sciences, 2024)
A very influential factor in marine fish production is the provision of efficient and appropriate feed and feed management for marine fish larvae. Natural feed has content that can meet the nutritional needs of marine fish larvae. One of the natural feeds that can be utilized in marine fish farming is rotifer (Brachionus plicatilis). This study aims to determine the laboratory scale culture technique of Brachionus plicatilis, determine the growth rate of Brachionus plicatilis with different phytoplankton feeding, determine the optimal phytoplankton density for Brachionus plicatilis. Data collection techniques in this study used 2 kinds of data, namely primary data and secondary data. Primary data comes from observation, interviews, and active participation. While secondary data comes from literature studies, namely books, journals, annual reports, theses, and so on. Laboratory-scale Brachionus plicatilis culture starts from sterilization of tools and materials, planting Brachionus plicatilis seedlings, feeding, and calculating the population of Brachionus plicatilis. Brachionus plicatilis fed with Nannochloropsis oculata at a density of 100,000 cells/ml entered the exponential phase on day 4 with a total number of individuals of 72 ind/ml, while Brachionus plicatilis fed with Tetraselmis chuii at a density of 3000 cells/ml entered the exponential phase on day 5 with a total number of individuals of 100 ind/ml.